2018
DOI: 10.21776/ub.jkb.2018.030.01.4
|View full text |Cite
|
Sign up to set email alerts
|

Kadar IL-6 dan IL-10 Serum pada Tahapan Inflamasi di Rattus norvegicus yang terinfeksi Candida albicans

Abstract: Insiden kandidiasis sangat tinggi di dunia yang disebabkan Candida albicans. Agen antifungi telah banyak dikembangkan, namun resistensi terhadap antifungi masih menjadi suatu permasalahan. Resistensi antifungi ini diakibatkan oleh kemampuan C. albicans dalam membentuk biofilm. Terbentuknya biofilm dari infeksi C. albicans diawali oleh proses inflamasi. Proses inflamasi oleh Candida albicans terjadi pada beberapa tahap yang salah satu indikatornya adalah dilepaskannya sitokin proinflamasi (IL-6) dan anti inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…In cell culture conditions, it cannot be determined whether IL-6 appears because it is proinflammatory or anti-inflammatory. IL-6 levels were higher in the PRP treatment group, which is the same as previous research that IL-6 concentrations increased in cultures with PRP treatment (Sundman et al, 2013;Kovacs et al, 2014;Masfufatun et al, 2018;Zongfei et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In cell culture conditions, it cannot be determined whether IL-6 appears because it is proinflammatory or anti-inflammatory. IL-6 levels were higher in the PRP treatment group, which is the same as previous research that IL-6 concentrations increased in cultures with PRP treatment (Sundman et al, 2013;Kovacs et al, 2014;Masfufatun et al, 2018;Zongfei et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Aloe vera has a significant stimulating effect on cell proliferation, migration of fibroblasts and keratinocytes, and research showed that Aloe vera can accelerate wound healing (Teplicki et al, 2018). Aloe vera stimulates fibroblasts which will produce new collagen during the wound healing process (Nimma et al, 2017) as confirmed by Alam (2019) that Aloe vera gel could affect the formation of wound collagen.…”
Section: Discussionmentioning
confidence: 85%
“…Conversely, the administration of Aloe vera caused lower IL-10 expression and higher IL-6 expression compared to honey. Both IL-6 and IL-10 are cytokines but have different roles where IL-6 is a pro-inflammatory cytokine, while IL-10 is an anti-inflammatory (Masfufatun, Tania, Raharjo, & Baktir, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of ECM on C. albicans biofilm is important as a shelter to evade the host's immune response and increases their resistance to antifungal drugs. In another study, the body's immune response begins in the early stages of C. albicans biofilm formation in the intestinal rats, so an immunomodulatory therapy can be developed against candidiasis to inhibit the formation of C. albicans biofilms [28].…”
Section: Biofilm Formation In the Intestinal Mucosamentioning
confidence: 99%